AN IMPROVED MODEL FOR THE CLASSIFICATION OF CREDIT RISK USING HYBRID DEEP LEARNING APPROACH - Ayodele, Emmanuel Oladimeji; Sholanke, Temitope Folasade; Idowu, Peter Adebayo (FUDMA Journal of Sciences, 2026)
This study identified credit risk factors in the Nigerian banking sector and developed a hybrid deep learning model to improve credit facility engagements. Both secondary and primary datasets were employed. Secondary data were sourced from selected commercial banks and peer-reviewed publications, while primary data were gathered through Key Informant Interviews (KII) with experienced commercial bankers. Categorical features underwent data transformation, and feature importance was assessed using mutual information, which informed the generation of a reformed dataset. A Hybrid Deep Learning classification model was formulated and simulated using varying proportions of the hold-one-out method via Google Colaboratory. Model performance was evaluated based on accuracy, true positive rate, false positive rate, and precision. Six key features were identified as most relevant to credit risk classification: monthly income, annual income, amount invested monthly, outstanding debt, equated monthly installments, and type of loan. The DNN-based model trained on these features achieved a prediction accuracy of 99.9%, significantly reducing redundancy across the original 23 features and cutting processing time. Furthermore, the Hybrid model (combining an AutoEncoder with a Deep Neural Network) outperformed a standalone DNN-based model by 46.8%. The study concluded that selecting relevant features for predictive modelling tasks reduces model complexity, simulation time, and memory usage, collectively contributing to improved performance. These findings offer a practical framework for enhancing credit risk assessment in the Nigerian banking sector through intelligent, efficiency-driven machine learning approaches.
Keywords: Credit Risk; Improved Model; Deep Learning; DNN-based Model